TANTANGAN DAN PELUANG EVALUASI PENDIDIKAN KARAKTER DI SEKOLAH DI ERA MODERN - Dita Durotun Nufus; Fatimah Tur Rizqi; Enung Nugraha; Umi Kultsum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Character education is an important aspect of the education system that aims to shape individuals with good morals, ethics, and values. The implementation of character education in schools faces several challenges, such as a lack of resources, a lack of awareness of the importance of character education, and a lack of teacher ability to implement character education. Evaluating character education becomes very important to determine the extent to which character education has been successfully implemented and to identify areas that need improvement. This research aims to analyze the implementation of character education in schools and identify the challenges faced in its implementation. The research results indicate that character education can be effectively implemented thru the integration of character values into the curriculum, extracurricular activities, and school culture. Character education can be evaluated thru observation, assessment, and self-evaluation to determine the extent to which character education has been successfully implemented.